Content evaluation of the inclusive eHealth guide: how to develop interventions for people with a lower socioeconomic position? - Al-Dhahir, Isra; Breeman, Linda D.; Faber, Jasper S.; Wentzel, Jobke; van den Berg-Emons, Rita J. G.; Kraal, Jos J.; Janssen, Veronica R.; Kraaijenhagen, Roderik A.; Visch, Valentijn T.; Chavannes, Niels H.; Evers, Andrea W. M. (Frontiers in Digital Health, 2025)
ObjectiveseHealth interventions favor those with higher socio-economic positions (SEPs). This can widen disparities, as people with lower SEPs may lack resources and face digital or financial barriers, making tailored solutions necessary. This study evaluates professionals' perceptions of the Inclusive eHealth Guide (IeG) regarding its content. The aim was to ensure it meets the needs of professionals and the targeted lower SEP demographic, thereby enhancing the effectiveness of eHealth interventions.MethodsThis mixed-method study used qualitative research through semi-structured interviews and the think-aloud method with 13 professionals involved in eight different eHealth lifestyle interventions using the eHealth guide. Quantitative feedback was obtained through a survey with evaluative multiple-choice questions. Participants evaluated the IeG at various stages. They identified positive aspects and points for improvement, and provided recommendations for the guide's content and structure.ResultsParticipants valued the IeG's practicality and comprehensiveness, noting its usefulness in developing accessible eHealth solutions for populations with lower SEP. They suggested improving content clarity, expanding informational depth, and refining the guide's structure.ConclusionsThe IeG has potential as a valuable tool for professionals developing eHealth interventions for lower SEP populations. Continuous refinement is crucial to ensure the guide remains relevant and effective, contributing to reducing health disparities.